Christian Ethics, Trauma, and Dust in the Blood: Moving Toward Enfleshed Counter-Memory - Stephanie C. Edwards (Journal of Moral Theology)
While presenting very real medical and religious challenges, theology tends to both over-psychologize and over-spiritualize mental health suffering. Inspired by Jessica Coblentz’s theology of depression, articulated most thoroughly in _Dust in the Blood_, I expand her analysis to the field of trauma studies. Reading trauma with Coblentz clearly calls theology to account for its ongoing insufficient responses to real persons in pain. It also further exposes the metaphysical/ existential import of mental health writ large. To begin to address this void, I outline a Christian social ethic that calls the wider community to work for justice in contexts of suffering and facilitate spaces for potential healing when such justice is impossible. I call this ethic “enfleshed counter-memory.” Christian theology, as read by Coblentz, requires an ethic that can respond within the “wilderness” as well as point beyond its borders. Such an ethic has the capacity to enliven theological scholarship and practice to rightly respond to the ongoing global mental health crisis.